Мотивація персоналу через навчання - Лінькова, Олена Юріївна (Видавничий дім "Інтернаука", 2021)
У статті досліджено значення мотиваці персоналу для забезпечення гнучкості підприємства. Метою розвитку підприємства є прискорення процесів адаптаці до ринкових змін. Запропоновано модель мотиваці персоналу на основі реалізаці системи навчання, яка містить: дослідження ринкового попиту та споживчих цінностей; аудит кадрового потенціалу; формування системи навчання за проектом навичок; оцінку ефективності програми навчання. Необхідними умовами ефективної мотиваці є: позитивні взаємовідносини менеджера з підлеглими; система навчання; корпоративна культура. Ціннісні орієнтаці (наділення людей позитивними якостями; ставлення до працівників як до особистості, що постійно розвивається; визнання і позитивне використання індивідуальних відмінностей; ефективне вираження і використання можливих почуттів; акцентування реальної поведінки; використання статусу тільки для організаційних цілей; довіра до людей; готовність відстоювати свою думку та йти на ризик; розгляд участі у даному процесі в якості істотно важливого для ефективного виконання завдання; акцент на співпрацю) максимально враховані в запропонованій моделі мотивації персоналу через навчання. Заходами щодо мінімізаці ризиків запровадження системи навчання є: командна робота; формування структурного підрозділу коучів; укладення довгострокових угод на визначені програми навчання. Ефективна реалізація системи навчання персоналу дозволить закласти основу мотиваці та забезпечити успіх бізнесу за рахунок: покращення результатів кадрового планування; удосконалення системи підбору персоналу; максимального використання потенціалу персоналу при досягненні цілей організації створення позитивного соціально-психологічного клімату в колективі; підвищення кваліфікації відчуття професійної відповідальності та ініціативності персоналу; усвідомлення соціального значення отриманих результатів та престижності даної роботи. Перспективи подальших досліджень у даному напрямку — це удосконалення технік навчання менеджерів.

The article examines the importance of staf motivation to ensure the flxibility of the enterprise. The purpose of the company’s development is to accelerate the processes of adaptation to market changes. A model of personnel motivation based on the implementation of the training system is proposed, which contains: research of market demand and consumer values; audit of human resources; formation of a system for teaching skills to the project evaluating the effctiveness of the training program. The necessary conditions for effctive motivation are: a positive relationship between the manager and subordinates; education system; corporate culture. Value orientations (endowing people with positive qualities; treating employees as a constantly developing personality; recognizing and positively using individual diffrences; effctively expressing and using possible feelings; emphasizing real behavior; using status only for organizational purposes; trust in people; willingness to defend one’s point vision and take risks; consideration of participation in this process as important for the effctive execution of the task; emphasis on cooperation) are maximally taken into account in the proposed model of personnel motivation through training. Measures to minimize the risks of implementing the training system: teamwork; formation of a structural unit of trainers; signing of long-term agreements on certain training programs. Effctive implementation of the personnel training system will create a basis for motivation and ensure business success by: improving the results of personnel planning; improvement of the personnel selection system; make the most of the potential of the personnel in achieving the goals of the organization; create a positive social and psychological climate in the team; improve the qualifiations, sense of professional responsibility and initiative of the staff awareness of the social signifiance of the results obtained and the prestige of this work. The prospect of further research in this direction is the improvement of training techniques for managers.
Staff motivation through training
Keywords: мотивація; навчання персоналу; гнучкість підприємства; корпоративна культура; motivation; personnel training; enterprise flexibility; corporate culture